Pengembangan Bahan Ajar PAI Berbasis Aplikasi Canva di MTs Ziyadatut Taqwa Pamekasan - Qulub, M. Nuril; Zainab, Nurul; Sarkawi, Ach. (Seutia Hukamaa Cendekia, 2024)
This research examines the development of Islamic Religious Education (PAI) teaching materials based on the Canva application in class VII of Madrasah Tsanawiyah (MTs) Ziyadatut Taqwa, Tlanakan Pamekasan. The background to this research is the lack of creativity in preparing teaching materials at the school, which impacts students' low enthusiasm for learning. This research uses the Research and Development (R&D) method with a modified Brog & Gall development model. Data was obtained through observation, interviews with teachers and students, and testing Canva-based teaching material products. Validation was carried out by teaching materials and material experts, resulting in a 75% and 85% feasibility percentage. The research results show that teaching materials based on the Canva application are very suitable for use, with a student eligibility percentage reaching 90%. Implementing this teaching material is hoped to increase students' understanding and enthusiasm for learning PAI.